Biomedical engineering systems and technologies : 5th International Joint Conference, BIOSTEC 2012, Vilamoura, Portugal, February 1-4, 2012, Revised Selected Papers - Schier, Jan; Huffel, Sabine; Conchon, Emmanuel; Correia, Carlos; Fred, Ana; Gamboa, Hugo; Gabriel, Joaquim (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 5th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2012, held in Vilamoura, Portugal, in February 2012. The 26 revised full papers presented together with one invited lecture were carefully reviewed and selected from a total of 522 submissions. The papers cover a wide range of topics and are organized in four general topical sections on biomedical electronics and devices; bioinformatics models, methods and algorithms; bio-inspired systems and signal processing; health informatics.